2023
DOI: 10.1021/acs.est.3c01538
|View full text |Cite
|
Sign up to set email alerts
|

Drought Alleviates the Negative Effects of Microplastics on Soil Micro-Food Web Complexity and Stability

Abstract: Soil ecosystems are under considerable pressure due to anthropogenic factors, including microplastics (MPs) pollution and drought. However, little is known about the interactive effects of MPs and drought on soil organisms, especially soil micro-food web. We conducted a microcosm experiment with MPs pollution (including two types and two sizes of MPs) and drought to investigate their interaction effects on soil microbial, protist, and nematode communities in soil micro-food web. We found that MPs significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 73 publications
2
1
0
Order By: Relevance
“…In the present study, the addition of pure MPs induced negative effects on the plant bacterial microbiome. This was reported to be true even in larger soil microfood networks, including soil bacteria, fungi, protists, and nematode communities . In agreement with Liu et al, in the present work MPs decreased the stability of microbial- and microfood networks, with smaller MPs having stronger negative effects than larger MPs.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, the addition of pure MPs induced negative effects on the plant bacterial microbiome. This was reported to be true even in larger soil microfood networks, including soil bacteria, fungi, protists, and nematode communities . In agreement with Liu et al, in the present work MPs decreased the stability of microbial- and microfood networks, with smaller MPs having stronger negative effects than larger MPs.…”
Section: Resultssupporting
confidence: 93%
“…This was reported to be true even in larger soil microfood networks, including soil bacteria, fungi, protists, and nematode communities . In agreement with Liu et al, in the present work MPs decreased the stability of microbial- and microfood networks, with smaller MPs having stronger negative effects than larger MPs. For ryegrass in this study, a minor dose effect was observed for both the addition of NPs and MPs, which could singly and jointly increase plant growth.…”
Section: Resultssupporting
confidence: 93%
“…Therefore, microplastics and drought effects on terrestrial systems are likely strongly modulated by soil biota. On the one hand, microplastics may affect the composition of soil bacterial communities by altering their abundance, diversity and activity with consequences for key processes such as nitrification (Fei et al, 2020; Huang et al, 2019; Seeley et al, 2020; Zhao et al, 2021), or potentially affect soil fungal communities as observed in aquatic systems (Kettner et al, 2017), with consequences on soil micro‐food webs (Liu et al, 2023). Indeed, research has shown that microplastics could accumulate fungal pathogens on their surfaces (Gkoutselis et al, 2021), leading to pathogen transfer into the soil matrix (Yu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%